2022
DOI: 10.1002/adom.202200704
|View full text |Cite
|
Sign up to set email alerts
|

An Overlooked Charge‐Transfer Interaction in the Interfacial Triplet–Triplet Upconversion Process in Blue Organic Light‐Emitting Diodes

Abstract: collide, alongside the formation of singlets and quintets, highly reactive "hot" triplets (>5 eV) would unwarrantedly be formed, leading to the rapid degradation of OLEDs. [5] Therefore, the control of overcrowded high-energy triplets has been the most critical issue for OLED research over the last 20 years. [4,[6][7][8] An alternative triplet-excitonic pathway in blue OLEDs is a triplet-triplet upconversion (TTU), which is a well-established solution for practical applications. [9,10] Anthracene derivatives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Recently, Nguyen et al reported that the charge transfer (CT) complexes generated at the interface between the electron blocking layer (EBL) and anthracene hosts could have a significant impact on efficiency enhancement. 39 Therefore, it is necessary to distinguish whether the high efficiency of the 2MIQ-NPA device is due to the hot exciton channel or the formation of CT complexes. In order to investigate the formation of CT complexes, the PL and time-resolved PL (TrPL) data of a single film of the EBL material (BPADBF) and mixed films with TTF-Phen and 2MIQ-NPA were carried out.…”
Section: Electroluminescence Properties Of Non-doped Devicesmentioning
confidence: 99%
“…Recently, Nguyen et al reported that the charge transfer (CT) complexes generated at the interface between the electron blocking layer (EBL) and anthracene hosts could have a significant impact on efficiency enhancement. 39 Therefore, it is necessary to distinguish whether the high efficiency of the 2MIQ-NPA device is due to the hot exciton channel or the formation of CT complexes. In order to investigate the formation of CT complexes, the PL and time-resolved PL (TrPL) data of a single film of the EBL material (BPADBF) and mixed films with TTF-Phen and 2MIQ-NPA were carried out.…”
Section: Electroluminescence Properties Of Non-doped Devicesmentioning
confidence: 99%
“…As a result, DABNA derivatives are now widely commercialised as blue emitters in triplet–triplet annihilation (TTA)-driven fluorescent devices for smartphones and televisions. 87–91 However, MR emitters have not been implemented as TADF emitters because of their rapid degradation through the long-lived T 1 state in TADF-OLEDs. 87 One of the most effective ways of realising reliable TADF devices is boosting the RISC of MR emitters.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an external quantum efficiency (EQE) of ∼12% in pure blue TTU-OLEDs has been demonstrated, and it is reported that device optimization enables an ultralong operational lifetime (1000,000 h) for blue TTU-OLEDs. ,, Because the probability of a TTU event should depend on triplet density inside an active layer, a design of a device architecture to enable the dense accumulation is essential. For instance, a double emitting layer (EML) system has been proposed to ensure the highly dense triplet generation in the EML. , Further, our previous studies have demonstrated that the TTU process at the hole-transporting layer (HTL) and EML interfaces is highly efficient if there is a charge-transfer (CT) interaction present at the interface, leading to a dense accumulation of triplet that trigged TTU events at the interface . However, despite the theoretical upper limit of the TTU contribution yield being expected to be 60%, , blue OLEDs with maximum TTU contribution are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…27,33 Further, our previous studies have demonstrated that the TTU process at the hole-transporting layer (HTL) and EML interfaces is highly efficient if there is a charge-transfer (CT) interaction present at the interface, leading to a dense accumulation of triplet that trigged TTU events at the interface. 34 However, despite the theoretical upper limit of the TTU contribution yield being expected to be 60%, 27,35 blue OLEDs with maximum TTU contribution are still scarce.…”
Section: ■ Introductionmentioning
confidence: 99%